BERZIARAH KE MAKAM SYEKH YUSUF AL-MAKASSARI: Kajian Sosial-Ekonomi - Azis, Muhammad Nur Ichsan (Program Studi Sejarah Peradaban Islam Institut Agama Islam Darullughah Wadda'wah, 2024)
The study investigates the implications of undertaking a pilgrimage to the tomb of Syekh Yusuf Al-Makassari, whose significant contributions have profoundly shaped Islamic thought and civilization. Following his passing, his burial site has become a crucial destination for pilgrims, leading to socio-economic effects on the surrounding community. Employing historical methodologies within a socio-economic framework, the research aims to elucidate the socio-economic conditions of the community surrounding Sheikh Yusuf Al-Makassari's tomb. Recognized as a pivotal figure and scholar in Indonesian history and beyond, Sheikh Yusuf's enduring influence is evident through the influx of pilgrims from diverse regions to his gravesite, highlighting his ongoing societal significance. The findings of this study reveal various social and economic aspects, including the financial status of the local population, employment opportunities, and microeconomic dynamics.